INNOVATIVE TEACHING STRATEGIES FOR PRODUCTIVE SKILLS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Abduvasitov Abduraxim Abbasxanovich (University Research Base, 2024)
In order to improve productive skills in teaching English as a foreign language (EFL), this article examines creative teaching strategies. It looks at how technology can be used in conjunction with communicative language teaching (CLT), learner autonomy, project-based learning (PBL), neuroscience and psychology insights, and content-based instruction (CBI). By utilizing these strategies, teachers can establish dynamic and captivating learning spaces that promote language learning, critical thinking, and practical application. The paper underlines how crucial it is to modify instructional strategies to accommodate students' varied needs and preferences in a society where connectivity is gaining ground.